Partnerships and development policies in Greece: a firms' appreciation using CFA analysis - Theodore Metaxas; Marie Noelle Duquenne (European Regional Science Association (ERSA), 2013)
As very important for the materialization of local development and competitiveness policies is regarded the role of local authorities, especially with regards to the planning of and the implementation of local initiatives, promotion strategies and the city image on international level as well. This reflects the drive for growth mixed with the attempt to increase social responsibility, decrease worklessness and increase local entrepreneurship. The main priority of planning and developing these strategies focuses on the viable development of the local societies with an emphasis on more than just the economic development, since the existence of local authorities with entrepreneurial orientation derives as a basic need, mainly the last twenty years. In addition, partnerships are vital to any sustainable redevelopment program because they foster communications and the building of cooperation and trust between relevant stakeholders. Groups such as community development organizations, chambers of commerce, or business councils can contribute to the process of local economic development. The present research investigates the importance of selected local development policies for SME enterprises in Thessaloniki one of the metropolis of south Europe. The field research has been implemented by administering questionnaires on a representative sample of 227 enterprises. These enterprises have been selected through a stratified random sampling where strata are related to the main economic sector. The added value of this research is essential since there are only few similar researches in South east Europe and in Greece. The present research brings on important issues and questions about local economic development because it presents directly the estimations and views of a large number of local enterprises that reflect the image of local economy. Finally, this research gives a satisfactory overview of the inner growth of Thessaloniki and further the results could lead to an evaluation, planning, implementation, rejection or reconstruction of specific actions and policies locally. Further to EFA analysis, a Confirmatory Factor Analysis (CFA) has been implemented for two groups of firms: the ones having already developed active partnerships with local groups or actors and the other ones without such an experience. Through CFA, the objective is not only to appreciate which of the initial variables (reflecting alternatives policies) affect intensively the EFA components but also to assess which policies are perceived by firms as the most determinant in terms of partnerships' development and improvement of competitiveness according to their sector of operation.
Keywords: 330; Partnerships; development policies; empirical research; firms; Greece; Thessaloniki; Comfirmatory Factor Analysis